Emotional Intelligence and Numerical Abilities: How are They Related? - Aspriyani, Riski; Hartono, Bryan Pudji (Jurnal Pendidikan MIPA, 2022)
This Ex Post Facto research aims to determine the correlation between emotional intelligence and students' numerical abilities and the strength of the correlation between the two variables. Data collection was carried out on seventh-grade students at MTS N 7 Sleman Yogyakarta with a total of 35 respondents. The sampling technique used was simple random sampling. Respondents were given an emotional intelligence questionnaire and a numerical ability test whereas previously the instruments were tested for validity and reliability. The data analysis technique in this study uses Simple Linear Correlation. Prerequisites that must be met before the significance test is a linearity test and a normality test. Using the product moment/Pearson correlation, the result is that the rxy value is 0.547. Also, obtained the value of sig. of 0.001 < 0.05 or the value of F = 12.824 > 4.17 as a result H0 is rejected. This study concludes that there is a positive correlation between emotional intelligence and students' numerical ability with a strength of 0.547. This means that the higher the emotional intelligence possessed, the higher the student's numerical ability. The value of the coefficient of determination (R2) is 29.90%, which means that the emotional intelligence variable affects students' numerical abilities by 29.90%, thus 71.10% is influenced by other variables.Keywords: emotional intelligence, numerical abilities, Pearson correlation.DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp918-929